Clinical course and outcomes of simultaneous-versus staged-bilateral medial opening wedge high tibial osteotomy - Hiroyasu Ogawa; Kazu Matsumoto; Masaya Sengoku; Hiroki Yoshioka; Kyosuke Yamamoto; Tetsuya Shimokawa; Kazuichiro Ohnishi; Haruhiko Akiyama (Elsevier, 2021)
Background: Difference in the clinical course and outcomes between simultaneous- and staged-bilateral medial opening wedge high tibial osteotomies (OWHTOs) over time was unknown. The study hypothesis was that patients who underwent simultaneous-bilateral OWHTO (SMBO) have a more rapid improvement in knee function than those who underwent staged-bilateral OWHTO (STBO) due to difference in the change of lower limb alignment between SMBO and STBO. Methods: The records of 56 knees in 28 patients who underwent either SMBO (n = 28) or STBO (n = 28) were retrospectively analysed. The time course data of weight-bearing line percentage (%WBL), joint line convergence angle (JLCA), and Knee Society Score were compared between the two procedures. Results: Hospitalisation for SMBO was longer than that for STBO by 1 week. No significant difference was observed in %WBL between the two procedures. The JLCA was significantly lower with SMBO than with the first-stage surgery of STBO (P < 0.05), but it became equivalent in both groups at the last follow-up. The knee scores in both SMBO and the first-stage surgery of STBO significantly improved in approximately 1 year. The function scores in the first-stage surgery of STBO did not significantly improve until the completion of the second-stage surgery whereas those in SMBO significantly improved 1 year after surgery and become stable. The function score 1 year after surgery was significantly higher in SMBO than in the first-stage surgery of STBO (p < 0.001). Conclusions: Although both SMBO and STBO achieved the desired therapeutic results, SMBO led to earlier functional improvement and decreased JLCA compared with STBO.